An Evaluation To The Historical Objection of The Seventh-Day Adventist Doctrine of The Pre-Advent Investigative Judgment - Simanjuntak, Mangara Juara (11th International Scholars Conference, 2019)
The Seventh-day Adventist doctrine of the pre-advent investigative judgment has been attacked by some former Adventist members. Desmond Ford, one of the opponents, doubted the historical basis of the doctrine. He argued that this Adventist’s distinctive doctrine highly relies upon and can merely be proven from E. G. White’s writings. He claimed that the Millerites and the early Sabbatarian Adventist did not teach this teaching. No references in their writings explained this doctrine. The purpose of this study is to present historical facts from the writings of Adventist pioneers as an evaluation to the objection. This study is a historical approach using documentary research method. From each development stage of the view, researcher uses primary resource. The researcher also employs the secondary resources only to see current opinion about the subject. From the historical facts, it is found that the teaching of the pre-advent investigative judgment has been taught before E. G. White wrote it. Some Millerites and early Sabbatarian Adventists employed several terms to express the concept, such as the typical Day of Atonement, breastplate of judgment, announcement of God’s judgment hour, scene of God’s, Christ’s parable of the wedding ceremony, judgment of the “house of God”, the term “Laodicea”, and God’s rewards either for salvation or punishment at the second coming of Christ. Thus, it is evident that before E. G. White wrote about the pre-advent investigative judgment, some Millerites and early Sabbatarian Adventists have already mentioned it in their writings. The terms used by Millerites and Sabbatarian Adventists to describe the teaching of the pre-advent investigative judgment are important to prove that the doctrine is not merely derived from E. G. White.